Hematological and Molecular Characterization of Hb J-Buda [α61(E10)Lys → Asn, AAG > AAT] - Panyasai S. (2017)
© 2016, Indian Society of Haematology & Transfusion Medicine. Hemoglobin (Hb) J-Buda [α61(E10)Lys → Asn, AAG  >  AAT] is a very rare α-chain variant found in South-East Asia. We analyzed hematological parameters and provided a rapid molecular analysis method for detection of this hemoglobinopathy in two Thai women who had severe microcytic anemia with Hb and MCV < 70 g/L and 80 fL, respectively. The HPLC revealed an abnormal Hb peak eluted ahead of HbA at retention time of 1.91–1.98 min. On CE, the abnormal Hb peak was observed at the electrophoretic zone 12 which corresponded to Hb Bart’s. The DNA sequencing revealed the AAG → AAT mutation at codon 61 for Hb J-Buda on one allele of the α1-globin gene. The developed Allele-specific PCR (ASPCR) showed the 455 bp amplified fragment from Hb J-Buda allele. Thus, understanding of hematological characterizations and the developed ASPCR for diagnosis of Hb J-Buda are essential for genetic counseling of this hemoglobinopathy.